A new multilayered visco‐elasto‐plastic experimental model to study strike‐slip fault seismic cycle. Issue 2 (12th February 2015) - Caniven, Y.; Dominguez, S.; Soliva, R.; Cattin, R.; Peyret, M.; Marchandon, M.; Romano, C.; Strak, V.
Abstract: Nowadays, technological advances in satellite imagery measurements as well as the development of dense geodetic and seismologic networks allow for a detailed analysis of surface deformation associated with active fault seismic cycle. However, the study of earthquake dynamics faces several limiting factors related to the difficulty to access the deep source of earthquake and to integrate the characteristic time scales of deformation processes that extend from seconds to thousands of years. To overcome part of these limitations and better constrain the role and couplings between kinematic and mechanical parameters, we have developed a new experimental approach allowing for the simulation of strike‐slip fault earthquakes and analyze in detail hundreds of successive seismic cycle. Model rheology is made of multilayered visco‐elasto‐plastic analog materials to account for the mechanical behavior of the upper and lower crust and to allow simulating brittle/ductile coupling, postseismic deformation phase and far‐field stress transfers. The kinematic evolution of the model surface is monitored using an optical system, based on subpixel spectral correlation of high‐resolution digital images. First, results show that the model succeed in reproducing the deformation mechanisms and surface kinematics associated to the main phases of the seismic cycle indicating that model scaling is satisfactory. These results are comforted by using numerical algorithms to study the strain and stress distribution at the surface and at depth, along the fault plane. Our analog modeling approach appears, then, as an efficient complementary approach to investigate earthquake dynamics. Key Points: Seismic cycle on a strike‐slip fault is simulated using a new experimental model Realistic rheologic, tectonics and kinematics boundary conditions are used Main mechanisms and kinematics related to the seismic cycle are well reproduced